Small ruminant production - the present situation and possible nutritional interventions for improvement - Reynolds, L. (1986)
Discusses the present situation of small ruminant production and possible nutritional interventions for improvement in tropical Africa. Includes data on ruminant livestock population by species and ecologcal zone; the effect of alley farming on the yield of maize; and the effects of supplementary Leucaena and Gliricidia with ad-libitum Panicum maximum on the produtivity of West African Dwarf sheep.